Implementasi Program Pendidikan Individual (PPI/IEP) pada Anak Berkebutuhan Khusus: Sebuah Studi Kualitatif: Studi di Kota Banda Aceh - Riefky Aulia; Sri Nurhayati Selian (International Forum of Researchers and Lecturers, 2026)
The Individualized Education Program (IEP), known in Indonesia as Program Pendidikan Individual (PPI), is a learning-planning instrument specifically designed to address the personalized learning needs of children with special needs. Although its use has been widely encouraged within Indonesia's inclusive education policy, its implementation in the field still faces various challenges, particularly at schools that lack adequate support systems. This study aims to explore how teachers in Banda Aceh City understand, design, and implement IEPs for students with special needs, as well as the obstacles they encounter in the process. This research employs a descriptive qualitative approach involving five teachers selected through purposive sampling as informants. Data were collected through observation and semi-structured interviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings indicate that IEP implementation in practice remains heavily dependent on individual teacher initiative, involves minimal multidisciplinary collaboration, and is constrained by limited time, training, and family support. These findings offer an initial picture of the gap between policy ideals and the reality of IEP implementation at the school level, while also informing the development of more structured teacher mentoring systems for educating children with special needs.